Local Content-Integrated STEM-PjBL for Enhancing Higher-Order Thinking Skills in Physics - Pathoni, Haerul; Asyhar, Rayandra; Maison, Maison; Huda, Nizlel (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Higher-order thinking skills (HOTS) are essential in physics education but remain insufficiently developed through conventional instruction. Although STEM-integrated Project-Based Learning (STEM-PjBL) has been widely recognized for promoting higher-order cognitive skills, limited empirical evidence has examined the integration of local cultural content within this approach. This study investigated the effectiveness of a local content-integrated STEM-PjBL model based on Jambi Malay culture in enhancing students' HOTS. A one-group pretest-posttest pre-experimental design was conducted with Physics Education students at Universitas Jambi. Data were collected using a HOTS-based written test and analyzed through descriptive and inferential statistical procedures to examine changes before and after the intervention. The findings demonstrated consistent improvements in students' HOTS following the implementation of the learning model. Students showed stronger abilities to analyze, evaluate, and apply physics concepts to authentic problems while connecting scientific knowledge with culturally meaningful contexts through project-based activities. The integration of Jambi Malay local content created more contextual and engaging learning experiences that encouraged critical thinking, collaboration, and authentic problem solving. These findings provide empirical evidence that local content-integrated STEM-PjBL offers an effective pedagogical framework for promoting higher-order thinking in physics education while simultaneously strengthening students' appreciation of local culture.